Efektivitas Pembelajaran IPA Berbasis Etno-STEM dalam Melatihkan Keterampilan Berpikir Analisis - Septi Budi Sartika; Nur Efendi; Fitria Eka Wulandari (Universitas Muhammadiyah Ponorogo, 2022)
Natural science is a subject that can be delivered through various strategies in understanding the concept, one of which is through ethno-STEM, with Sidoarjo local wisdom that is packed integrated with science, technology, engineering, and mathematics. This strategy is done to practice analytical thinking skills. The purpose of the study to describe the effectiveness of natural science learning based ethno-STEM to practicing the analytical thinking skills of secondary school students. The research method uses quantitative research type experiments with one group pretest and posttest design, class VIII student population of 120 students with a sample of grade VIII B a number of 30 students in MTs Muhammadiyah 1 Taman Sidoarjo. Research procedures include pretest, treatment by implementing natural science learning based ethno-STEM, and posttest. Data analysis techniques use descriptive statistics. The results showed that the implementation of naturak science learning based ethno-STEM is said to be effective, namely 1) the implementation of average learning 3.7 very well categorized, 2) student activities relevant to the average learning 3.6 categorized very well, 3) there is an increase in the value of analytical thinking skills of students by 0.6 moderate category, and 4) positive student response to learning by 90%. Further research is expected to be able to compare treatment between classes, as well as other variables that contribute to learning so that the analysis will be deeper.